2020
DOI: 10.1002/qj.3844
|View full text |Cite
|
Sign up to set email alerts
|

Recent upgrades to the Met Office convective‐scale ensemble: An hourly time‐lagged 5‐day ensemble

Abstract: In this article, we introduce a new configuration of the Met Office convective‐scale ensemble for numerical weather prediction, for the Met Office Global and Regional Ensemble Prediction System over the United Kingdom (MOGREPS‐UK). The new version, which became operational in March 2019, uses an hourly time‐lagged configuration to take advantage of the hourly 4D‐Var data assimilation run in the deterministic UK model with variable horizontal resolution, the UKV. An 18‐member ensemble is created by running thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…Arguably, the most appealing way to improve CP ensemble spread is way to improve the CP ensemble spread is to improve the spread of the initial conditions of the parent driving ensemble. Porson et al (2019), for instance, showed that that perturbing the sea surface temperatures (SSTs) in the initial conditions of the parent model generates a higher spread also in the driven CP ensemble than just having fixed SSTs. Another way to enhance the ensemble spread is through the representation of model error in the physics scheme (Bouttier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arguably, the most appealing way to improve CP ensemble spread is way to improve the CP ensemble spread is to improve the spread of the initial conditions of the parent driving ensemble. Porson et al (2019), for instance, showed that that perturbing the sea surface temperatures (SSTs) in the initial conditions of the parent model generates a higher spread also in the driven CP ensemble than just having fixed SSTs. Another way to enhance the ensemble spread is through the representation of model error in the physics scheme (Bouttier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The simulations supporting the SWIFT forecasting testbed were run from 19 April to 12 May 2019, giving a total number of 24 days. The Met Office Unified Model (MetUM) Tropical East Africa CP ensemble model (hereafter CP-ENS) was run as a downscaler of the of the global ensemble, similar to the set-up used by the Met Office CP model (MOGREPS-UK) up to March 2016 (Hagelin et al 2017) and for the CP model over Singapore (Porson et al 2019). Here, the initial and boundary conditions for each CP-ENS member are taken from the MetUM global ensemble (MOGREPS-G, Bowler et al (2009), running with a horizontal grid spacing of 0.288 with 18 members.…”
Section: ) Forecastsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a strong requirement to move to the assessment of land surface and river flow simulations in probabilistic terms. Work is in progress to run the UK coupled system in ensemble mode, with the atmosphere component driven by the MOGREPS-UK operational NWP ensemble (Porson et al, 2020). Driving regional river flow predictions with an ensemble of precipitation input, and introducing stochastic and parameter perturbations in the land surface and river routing components offers many opportunities to better understand the propagation of uncertainty through the system, as well as consider appropriate design of regional coupled ensemble systems when coupling a range of potential flow solutions with ensemble ocean model components.…”
Section: Towards More Useful Coupled System Hydrological Predictionsmentioning
confidence: 99%
“…This study utilises 10‐m wind speed forecasts extracted from the Met Office's global ensemble prediction system, MOGREPS‐G (Walters et al ., 2017; Porson et al ., 2020), issued in the 2‐year period between January 1, 2018 and December 31, 2019. No major model upgrades have been performed since this period, and hence the model configuration is very similar to that currently in operation.…”
Section: Datamentioning
confidence: 99%